Low-Calorie Coal Liquefaction Products as an Alternative Fuel Oil - Yulfi Zetra; Anis Febriati; Dyah Nirmala; Rafwan Year Perry Burhan; Arizal Firmansyah; Zjahra Vianita Nugraheni (Universitas Gadjah Mada, 2022)
Liquefaction of low-rank coal has been done to optimize the utilization of low-rank coal, which is less economical for obtaining alternative fuel oil. Coal samples were taken from the Bukit Pinang coal mine, Samarinda Ulu, East Kalimantan. Coal was liquefied using the NEDOL procedure at PUSPITEK, Serpong, South Tangerang, Indonesia. This Bukit Pinang coal liquefaction produces five fractions consisting of Naphta, Light Oil (LO), Middle Oil (MO), Heavy Oil (HO), and Coal Liquid Bottom (CLB) fractions. The liquefaction yield was dominated by the HO and CLB fractions (> 50% by weight). The naphtha, MO and LO fractions were fractionated using SiO2 GF254 Thin Layer Chromatography (TLC) plate. It produced aliphatic and aromatic hydrocarbon fractions. Aliphatic hydrocarbon fractions were analyzed using a Gas Chromatography-Mass Spectrometer (GC-MS), while the aromatic hydrocarbon fractions were not analyzed. Mass spectrum studies showed that the components consisted of n-alkanes, isoalkanes (branched alkanes), cycloalkanes and alkyl cycloalkanes. The aliphatic hydrocarbon components resulting from the liquefaction of low-rank coal showed its equivalence with the components that make up fuel oil. Therefore, this coal liquefaction can be suggested as an optimization for low-rank coal, which is less economical.